Overview of hydrocolloid polymeric materials for biomedical applications: a review - Akkad, Haya; Ozerol, Esma Ahlatcioglu (TAYLOR & FRANCIS LTD, 2026)
Hydrocolloids are versatile materials widely used in many sectors such as food, wound healing systems, drug delivery systems, tissue engineering, pharmaceutical and environmental management due to their unique functional properties. Hydrocolloids are medical materials that play a vital role in the healing process and are available in various types, especially hydrocolloid wound healing systems hydrocolloid drug delivery systems and tissue engineering. These healing systems accelerate healing by providing a moist environment for wound healing, reduce pain and irritation, reduce the risk of infection and provide comfort to the patient. This article reviews the properties of hydrocolloids in the literature, their biomedical applications and the components, properties and advantages of healing systems and discusses the role of these healing systems. Hydrocolloid healing systems are made of materials such as carboxymethyl cellulose, gelatin, pectin, agar, sodium alginate, polyurethane, curdlan, Xanthan gum and QSH. This article also discusses the development of hydrocolloid healing systems, their place in modern wound care and new technological developments in this field. Proper selection and use of healing systems is critical to optimizing the healing process and this article aims to provide a comprehensive overview of this topic.
Keywords: Biopolymer; drug delivery system; hydrocolloid healing systems; tissue engineering; wound healing; DELIVERY-SYSTEMS; HYDROGELS; DRESSINGS; CHITOSAN; SCAFFOLD; FILMS; GUM; Materials Science; Polymer Science